Immigration and Bureaucratic Control : Language Practices in Public Administration. - Codó, Eva, 1971- (Language, Power & Social Process, v. 20., 2008)
This original study looks at language practices in a government agency responsible for granting or denying legal status to transnational migrants in Spain. Drawing on a unique corpus of naturally-occurring verbal interactions between state officials and migrant petitioners as well as ethnographic materials and interviews, it provides a fascinating insight into the relationship between language, social heterogeneity, and practices of exclusion. The book investigates how a national agency with homogenizing views of citizenship copes with the fundamental contradiction resulting from the state's c.